Restructuring the jail facility to fit with urban communities - Ramos, Almina Crista B. (College of Architecture, University of the Philippines Diliman, 2019)
This project aims to create a new approach in jail design so that jail facilities may serve their purpose, which isn't merely confining criminals to punish them, but also to shape them into law abiding citizens. Jail facilities, should fulfill its role of protecting the society by being a detention space for criminals, and by giving them a rehabilitative experience to prevent them from further committing crimes when they return to the community. Some of the problems in today's jail facilities are congestion, inhumane treatment, and lack of resources and facilities. Correctional facilities have always been excluded from communities and has created an unfavorable stigma that discriminates. By thinking beyond the conventional characteristics of jails such as sprawling development and structures that are isolated from the community, a new approach can be developed to enhance the efficiency of jails and optimization of resources. It must also take into account the universal purpose of jails, the objectives and mandates of the Bureau of Jail Management and Penology (BJMP), and site contexts.